The Relationships Between Mental Health and Violent Offending Among Serious Adolescent Offenders: An Examination of the Mediating Role of Experienced and Witnessed Victimization - Kim, Jihoon (Crime & delinquency, 2024)
Although a long line of research has examined the association between mental health and offending, previous literature primarily focused on the uni-directional path from mental health problems to offending, or vice versa. Also, there is still much to learn about how different types of victimization are related to the link between the two. To examine these questions, a series of fixed-effect models were employed to examine (1) the assessment of the relationship between mental health and violent offending and (2) the mediating role of experienced and witnessed victimization in that relationship. The results show a significant relationship between mental health and violent offending, while differences were found between the two types of victimization. Limitations and future research suggestions were discussed